Implementation of the Auditory Intellectually Repetition Method in BIPA Listening Learning with Tourism Content in Indonesia and Timor Leste at ESTVC. MM Lauala - Anita Naga , Yohana; Sulistiany Idris, Nuny; Whilky Rizkyanfi, Mochamad (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: To analyze the implementation and effectiveness of the Auditory Intellectual Repetition (AIR) method, integrated with tourism content from Indonesia and Timor-Leste, in improving Indonesian language proficiency among foreign language learners. Methods: A mixed-methods approach, combining classroom observations, pre-posttests, and semi-structured interviews, was employed with 30 BIPA learners at ESCTV.MM. Lauala-Gleno over a 12-week period. Results:The results indicated significant improvement in students' Indonesian language proficiency across all four language skills, with the most notable improvements in listening comprehension (M = 18.4, SD = 3.2) and speaking ability (M = 16.7, SD = 2.8), p < 0.001. Novelty: The AIR method with tourism content effectively enhances BIPA learning outcomes by providing culturally relevant and contextually meaningful materials that facilitate language acquisition through systematic auditory processing, intellectual engagement, and strategic repetition, offering a novel pedagogical approach for Indonesian language learning in Timor-Leste.